PFM.72 A retrospective descriptive analysis of anaesthesia for transvaginal cervical cerclage. (9th June 2014) - Modha, J; Burul, G; Forya, F; James, CP; David, AL; Dick, J; Wee, L
Abstract : Introduction: Transvaginal cervical cerclage (TVCC) is a common operation in pregnancy requiring an anaesthetic. Regional anaesthesia (RA) aims for T10 sensory blockade. 1 No data exists to guide the type of anaesthesia or intrathecal dose of local anaesthesia (IDLA) that should be employed for TVCC. 2 Aim: To determine the type of anaesthesia given for TVCC and the IDLA used for RA. Method: Ethical approval waived. Case notes of women having TVCC during pregnancy (January 2005–December 2012) were identified using the Obstetric Anaesthesia database and cross-referenced with the Preterm Birth clinic database. Analysis was conducted using Microsoft Excel. Results: In 165 women both general anaesthesia (n = 26, 16%) and RA (n = 139, 84%) were given at a mean gestational age of 16.6 weeks (range 9–23.6weeks). Of the RA group 95.7% were spinals, of which 5 women required a second anaesthetic procedure. There were no major anaesthetic complications and in all women TVCC was achieved successfully. Of the women receiving intrathecal anaesthesia 67.4% (93/138) documented IDLA. Hyperbaric bupivacaine 0.5% was used in all cases (mean dose 10.9mg, 6.5–15 mg). Both sensory block and IDLA was documented in 58% of intrathecal anaesthesia cases (54/93). The sensory block ranged from height T2–T12 and was not associated with IDLA, gestational age or body mass index at booking. Opiates were used in 73/93 women (78.5%), the most common being fentanyl (94%) with a mean dose of 20 mcg. Conclusion: In this series TVCC was performed safely under both general and RA. There is a wide variation in IDLA and sensory block. References: Chestnut P, Wong T. (2009) Chestnut's Obstetric Anesthesia: Principles and Practice, 4 th Edition, Philadelphia: Elsevier Cervical Cerclage, Green-top Guideline No 60, Royal College of Obstetricians and Gynaecologists, May 2011